Amanah Saham Nasional scheme / Rosiatimah Mohd Isa - Mohd Isa, Rosiatimah (1990)
The Amanah Saham Nasional scheme (ASN) is the largest unit trust scheme in the country which will reach its maturity date 31 Dec 1990. It was designed to accomodate the Bumiputera individuals participation through the process of saving on the basis for strengthening the community in the corporate sector and indirectly increases Bumiputera control over the companies in the country for long term. At the launching ceremony of the scheme in 1981, Datuk Seri Dr. Mahathir said that the success of the ASN scheme depends on the response and support given by Bumiputera themselves (The Star, 21 April 1981). Since it was introduced, the number of investors and total value of investments showed an increasing pattern. This is an indication of success of this ambitious scheme.